Co-Evolution of Parallel Triple Subduction Systems in the New Guinea Region: A Systematic Numerical Study - Wang, Liangliang; Dai, Liming; Gong, Wei; Li, Sanzhong; Jiang, Xiaodian; Dong, Hao; Wang, Di; Li, Fakun; Yu, Shengyao (Frontiers in Earth Science, 2022)
A specific configuration of the global subduction system is the parallel triple subduction. The widely accepted example of parallel triple subduction is the New Guinea Region, including a northward dip at the New Britain Trench (NBT), a southward dip at the Trobriand Trough (TT) and North Solomon Trench (NST). Questions regarding the parallel triple subduction system remain largely unexplored in terms of factors controlling its initiation, duration, and dynamics. Here, we use two-dimensional numerical models to study the dynamics mechanism of the parallel triple subduction system in the New Guinea Region. Four possible regimes are achieved: (i) the double subduction model, which includes the forward subduction jumping model (FSJ) and the subduction polarity reversal model (SPR); (ii) the parallel triple subduction model, which includes the tendency to forward jumping model (TFSJ) and the tendency to polarity reversal (TSPR). By evaluating the four regimes with actual seismic data, we suggest that the pre-existing rupture and the length of ocean-continent transition (OCT) determine the formation of the TT, while the formation of the NBT may be the result of the rheological strength differences between the Solomon Island Arc (SIA) and the Solomon Sea Basin (SSB); the initial length of the SSB can regulate the competitive relationship between the TT and NBT, which also determines the present-day inactive state of TT. A longer SSB makes TT and NBT are initiated independently, while a narrower SSB will allow interaction during subduction initiation of TT and NBT.